(untitled) (Hematology Meeting Reports, 2009)
There is little doubt that any gestation in mammalians (and thus also any new human life from its biological inception) can be considered as an haploidentical allo-transplant, due to the antigenic disparity existing between the pregnant mother (the host) and the embryo-foetus (the graft). Indeed in its obvious biological reality, the embryo-foetus, due to its antigenic constitution, is one half of paternal origin, thus foreign to the mother who, however, physiologically tolerates it. Therefore, little doubt exists that the concept, life itself is also an immunological phenomenon, may be extended also to prenatal life.1,2